Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To find the intercepts for the equation [tex]\(-x + 3y = 6\)[/tex], follow these steps:
### Finding the [tex]\(x\)[/tex]-intercept:
To find the [tex]\(x\)[/tex]-intercept, set [tex]\(y = 0\)[/tex] and solve for [tex]\(x\)[/tex].
1. Substitute [tex]\(y = 0\)[/tex] in the equation [tex]\(-x + 3y = 6\)[/tex]:
[tex]\[ -x + 3(0) = 6 \][/tex]
2. Simplify the equation:
[tex]\[ -x = 6 \][/tex]
3. Solve for [tex]\(x\)[/tex]:
[tex]\[ x = -6 \][/tex]
So, the [tex]\(x\)[/tex]-intercept is [tex]\((-6, 0)\)[/tex].
### Finding the [tex]\(y\)[/tex]-intercept:
To find the [tex]\(y\)[/tex]-intercept, set [tex]\(x = 0\)[/tex] and solve for [tex]\(y\)[/tex].
1. Substitute [tex]\(x = 0\)[/tex] in the equation [tex]\(-x + 3y = 6\)[/tex]:
[tex]\[ -0 + 3y = 6 \][/tex]
2. Simplify the equation:
[tex]\[ 3y = 6 \][/tex]
3. Solve for [tex]\(y\)[/tex]:
[tex]\[ y = \frac{6}{3} = 2 \][/tex]
So, the [tex]\(y\)[/tex]-intercept is [tex]\((0, 2)\)[/tex].
In summary:
- The [tex]\(x\)[/tex]-intercept is [tex]\((-6, 0)\)[/tex]
- The [tex]\(y\)[/tex]-intercept is [tex]\((0, 2)\)[/tex]
### Finding the [tex]\(x\)[/tex]-intercept:
To find the [tex]\(x\)[/tex]-intercept, set [tex]\(y = 0\)[/tex] and solve for [tex]\(x\)[/tex].
1. Substitute [tex]\(y = 0\)[/tex] in the equation [tex]\(-x + 3y = 6\)[/tex]:
[tex]\[ -x + 3(0) = 6 \][/tex]
2. Simplify the equation:
[tex]\[ -x = 6 \][/tex]
3. Solve for [tex]\(x\)[/tex]:
[tex]\[ x = -6 \][/tex]
So, the [tex]\(x\)[/tex]-intercept is [tex]\((-6, 0)\)[/tex].
### Finding the [tex]\(y\)[/tex]-intercept:
To find the [tex]\(y\)[/tex]-intercept, set [tex]\(x = 0\)[/tex] and solve for [tex]\(y\)[/tex].
1. Substitute [tex]\(x = 0\)[/tex] in the equation [tex]\(-x + 3y = 6\)[/tex]:
[tex]\[ -0 + 3y = 6 \][/tex]
2. Simplify the equation:
[tex]\[ 3y = 6 \][/tex]
3. Solve for [tex]\(y\)[/tex]:
[tex]\[ y = \frac{6}{3} = 2 \][/tex]
So, the [tex]\(y\)[/tex]-intercept is [tex]\((0, 2)\)[/tex].
In summary:
- The [tex]\(x\)[/tex]-intercept is [tex]\((-6, 0)\)[/tex]
- The [tex]\(y\)[/tex]-intercept is [tex]\((0, 2)\)[/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.